Epidemiological and medication profile of pediatric bacterial pneumonia hospitalizations: a narrative review - Ferreira , Ingryd de Sá Barreto; Carneiro, Ada Santos; Abrantes, Larissa Furtado; Estrela, Yahanna da Costa Anacleto; Assis, Elisângela Vilar de (Disciplinarum Scientia | Saúde, 2024)
Introduction: Among the infections that affect the lower respiratory tract, pneumonia stands out. Factors such as low birth weight, living in daycare centers, incomplete vaccination, previous episodes of pneumonia and environmental and socioeconomic issues lead to greater susceptibility to this disease and, consequently, an increase in infant morbidity and mortality. Objective: To identify the epidemiological and medication profile of hospitalizations for bacterial pneumonia in children, in order to facilitate early diagnosis and appropriate treatment. Methodology: This is a narrative, qualitative and descriptive review, using articles published between 2021 and 2023 that contain information on the epidemiological and drug profiles of pediatric bacterial pneumonia hospitalizations, searched in the following databases: BVS, Embase and PubMed. The following descriptors were used in the search: Clinical Epidemiology, Drug Therapy, Chemotherapy, Bacterial Pneumonia, Bacterial Pneumonia, Pediatrics, Hospitalization and Hospitalization. Results: 15 studies were included in this review. Regarding the epidemiological profile, there was a predominance of males and a mean age of 4.2 years, with heart disease and asthma as the most prevalent pre-existing comorbidities. As for the medication profile, treatment with macrolides prevailed, mainly azithromycin, for pneumonia caused by Mycoplasma pneumoniae and with aminopenicillins (amoxicillin and ampicillin) and cephalosporins for pneumonia caused by other bacteria. Conclusion: Pneumonia is a difficult disease to diagnose and often requires empirical treatment based on the possible causative agents. Therefore, knowledge of factors such as gender, age, immune status, the most common pathogens for the age group, the origin of the infection and pre-existing comorbidities is essential.